2022
DOI: 10.1093/ofid/ofac003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic-Associated Fatty Liver Disease Is Highly Prevalent in the Postacute COVID Syndrome

Abstract: Background Recently a proposal has been advanced to change the traditional definition of Non-Alcoholic Fatty Liver Disease (NAFLD) to Metabolic Associated Fatty Liver Disease (MAFLD), to reflect the cluster of metabolic abnormalities that may be more closely associated with cardiovascular risk. Long COVID is a smoldering inflammatory condition, characterized by several symptom clusters. This study aims to determine the prevalence of MAFLD in patients with post-acute COVID syndrome (PACS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…A study describing the clinical characteristics of patients with combined MAFLD and COVID-19 found more severe liver injury in MAFLD patients with COVID-19 than in uninfected MAFLD patients [114]. Moreover, another follow-up of 235 discharged patients with COVID-19 found that the prevalence of MAFLD at follow-up was 55.3%, which was greater than the prevalence of MAFLD at admission (37.3%) [115]. Therefore, special attention should be given to the management of patients with MAFLD during the COVID-19 pandemic.…”
Section: Interplay Between Mafld and Covid-19mentioning
confidence: 97%
“…A study describing the clinical characteristics of patients with combined MAFLD and COVID-19 found more severe liver injury in MAFLD patients with COVID-19 than in uninfected MAFLD patients [114]. Moreover, another follow-up of 235 discharged patients with COVID-19 found that the prevalence of MAFLD at follow-up was 55.3%, which was greater than the prevalence of MAFLD at admission (37.3%) [115]. Therefore, special attention should be given to the management of patients with MAFLD during the COVID-19 pandemic.…”
Section: Interplay Between Mafld and Covid-19mentioning
confidence: 97%
“…Being overweight before the pandemic was most likely to gain weight (65%) compared with those who reported being normal-weight (40%) [18] . A recent study reported that metabolic-associated fatty liver disease was highly prevalent at the time of hospital discharge and represented a specific post-acute COVID syndrome, which may affect increased mortality among survivors of COVID-19 [19] . Metabolic-associated fatty liver disease represented a specific post-acute COVID syndrome-cluster phenotype, with potential health consequences from cardiovascular and metabolic abnormalities in long-COVID-19 [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, MAFLD seems to be additionally highly prevalent after hospital discharge among patients infected with COVID-19. Specifically, the prevalence of MAFLD was 55 % in patients with Long-COVID-19, indicating the presence of a specific post-acute phenotype associated with higher risk for future metabolic and cardiovascular complications [111].…”
Section: Long-term Consequences and Management Of Nafld During The Pa...mentioning
confidence: 99%